RISK MANAGEMENT OF RAW MATERIAL PROCUREMENT IN MADUKISMO SUGAR FACTORY WITH THE HOUSE OF RISK METHOD - Gumono, Akhmad; Senjawati, Nanik Dara; Etikarini, Wulandari Dwi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Procurement of raw materials and sugarcane processing into sugar is an important part of the supply chain, which has the potential for various risks. Therefore, efforts are needed to gradually and continuously improve supply chain performance to overcome and prevent various risks. This research aims to (1) identify risk events and risk agents, (2) analyze risk agents that need to be prioritized for preventive action and (3) determine risk mitigation priorities in the procurement of sugar raw materials at the Madukismo Sugar Factory. The research method used is a descriptive case study method. Determining the criteria for risk events in the business process uses the Supply Chain Operation Reference (SCOR) dimensions. Risk agents and risk mitigation are analyzed using the House of Risk (HOR) method which consists of two phases. Based on the research results, 14 priority risk agents were found. Risk mitigation to address priority risk agents ranked 1-5 is: reformulating the SOP for cultivating seed sugarcane and milled sugarcane specific on Madukismo Sugar Factory, carrying out HR training, providing funds and production facilities on time, disciplining the implementation of SOPs through reward and punishment, and increasing supervision by each Plant Section personnel.